Confessions - Augustinus, Aurelius, Heiliger 354-430 (Hackett Publishing Company, Inc., 2019)
Front Cover -- Half Title -- Full Title Page -- Copyright Page -- Contents -- Introduction -- Essential Scriptures -- Notes on the Latin Text -- Notes on the Translation -- Abbreviations -- Suggestions for Further Reading -- Book One -- Book Two -- Book Three -- Book Four -- Book Five -- Book Six -- Book Seven -- Book Eight -- Book Nine -- Book Ten -- Book Eleven -- Book Twelve -- Book Thirteen -- Appendix A: Psalm 4 -- Appendix B: Psalm 41 -- Appendix C: Psalm 100 -- Appendix D: Reconsiderations, Book 2, Chapter 6 -- Topical Index -- Scriptural Index -- Back Cover.